Cosmopolitanism, cosmopolitics and indigenous peoples: elements for a possible alliance (Alternautas, 2022)
We are witnessing the re-emergence of cosmopolitism. Cosmopolitanism is rising as a politico-cultural movement, which while being globalised in the inter-metropolis connection, it chiefly reaffirms the normative engagement with human rights beyond national borders. Almost simultaneously, several theories have appeared under the term ‘cosmopolitical’. They question cosmopolitan common sense and its mono-naturalism as they reclaim the polyphonic de- and re-construction of the world from the heterogeneous forces and entities that inhabit it. Considering their dissimilar assumptions, cosmopolitanism and cosmopolitics do not seem to encounter points of convergence, except their aspirations to think about the world. For those who support cosmopolitanism, this is the field of human political action, while for advocates of cosmopolitics the world is something to be constructed by involving human and non-human actors. In this way, as suggested by Bruno Latour, it could be argued that we are obliged to decide between cosmopolitism and cosmopolitics; between assuming the urgency of saving the world and the slowing down of decisions that undermine this enterprise; between the ‘logical equivalence’ and the ‘operator of equality’ that Isabelle Stengers tells us about (2014).